PENDAPATAN USAHATANI PADI SAWAH DI SUBAK SEMBUNG KELURAHAN PEGUYANGAN KECAMATAN DENPASAR UTARA - Florianus Galgani; I Ketut Arnawa; I Made Sukerta (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2018)
Subak Sembung is an area located in the green area of Peguyangan urban village of Denpasar. One of the agricultural sub-sectors is rice crops because rice includes staple food which is very dominant to survive, so that rice farming is still the mainstay of farmers to fulfill their household needs and community needs. The purpose of this research is to know (1) paddy farming income income in Subak Sembung Kelurahan Peguyangan District of North Denpasar (2) level of efficiency value of paddy field farming in Subak Sembung Kelurahan Peguyangan District of North Denpasar. This research was conducted in Peguyangan Village, North Denpasar District of Denpasar Regency with